Principles of Robust Timing over the Internet. - RIDOUX, JULIEN; VEITCH, DARRYL (Communications of the ACM, 2010)
The article discusses how computer networks can be used to synchronize computer clocks. The authors discuss how personal computers (PCs) can access Network Time Protocol (NTP) servers to correct deviations in their internal clocks through the transfer of packet timestamps but suggest that NTP systems may not be accurate enough for computing in industries such as telecommunications and finance. They discuss how oscillators in PCs provide a source of time that can drift and note that synchronization algorithms must account for delay variations from timing packets due to elements such as network interface card (NIC) operations, the queuing of Internet Protocol (IP) routers and network congestion. Feedback and feed-forward methods for absolute clock synchronization are described.